Ceramide-antiestrogen nanoliposomal combinations – novel impact of hormonal therapy in hormone-insensitive breast cancer - Morad, Samy A.F. (2012)
Although the sphingolipid ceramide exhibits potent tumor suppressor effects, efforts to harness this have been hampered by poor solubility, uptake, bioavailability, and metabolic conversion. Therefore, identification of avenues to improve efficacy is necessary for development of ceramide-based therapies. In this study we used mutant p53, triple negative breast cancer (TNBC) cells, a type of breast cancer highly refractory to treatment, and cell-permeable nanoliposomal C6-ceramide in conjunction with the antiestrogen tamoxifen, which has been shown to be an effective modulator of ceramide metabolism. We show for the first time that nanoliposomal tamoxifen enhances nanoliposomal C6-ceramide cytotoxicity in cultured TNBC cells, a response that was accompanied by induction of cell cycle arrest at G1 and G2, caspase-dependent induction of DNA fragmentation, and enhanced mitochondrial and lysosomal membrane permeability, at 18 and 2 hr, respectively. Tamoxifen metabolites were also effective. Only tamoxifen promoted lysosomal membrane permeability. In addition, we demonstrate for the first time that tamoxifen inhibits acid ceramidase, as measured in intact cell assays; this effect was irreversible. Together, our findings show that tamoxifen magnifies the antiproliferative effects of C6-ceramide via combined targeting of cell cycle traverse and lysosomal and mitochondrial integrity. We adduce that C6-ceramide-induced apoptosis is amplified by tamoxifen's impact on lysosomes and perhaps accompanying inhibition of acid ceramidase, which could result in decreased levels of sphingosine 1-phosphate. This drug regimen could serve as a promising therapy for chemoresistant and triple negative types of breast cancer, and thus represents an indication for tamoxifen, irrespective of estrogen receptor status.